2010
DOI: 10.2215/cjn.03770609
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Therapy to Prevent Bone Mineral Density Loss after Kidney and Kidney-Pancreas Transplantation

Abstract: Background and objectives: Most patients who undergo kidney or kidney-pancreas transplantation have renal osteodystrophy, and immediately after transplantation bone mineral density (BMD) commonly falls. Together, these abnormalities predispose to an increased fracture incidence. Bisphosphonate or calcitriol therapy can preserve BMD after transplantation, but although bisphosphonates may be more effective, they pose potential risks for adynamic bone.Design, setting, participants, & measurements: A total of 153 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Our analysis adds to the evidence base for the safety of bisphosphonate use in kidney transplant recipients as we did not observe higher rates of allograft dysfunction or abnormalities in serum calcium levels. Clinicians should individualize decisions when considering the use of bisphosphonates in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis adds to the evidence base for the safety of bisphosphonate use in kidney transplant recipients as we did not observe higher rates of allograft dysfunction or abnormalities in serum calcium levels. Clinicians should individualize decisions when considering the use of bisphosphonates in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…4 ) [86][87][88] , thereby becoming a well-accepted preventive therapy against bone loss in KTRs with osteopenia or osteoporosis [30,89] . A clinical investigation by Gonzalez et al [74] reported that paricalcitol induced a 30% reduction of PTH levels in 78% of 58 KTRs at 24 months of follow-up, although no data were provided on the BMD trend.…”
Section: Interventional Studies With Native and Active Vitamin D For mentioning
confidence: 99%
“…93 Most patients who undergo kidney or kidney-pancreas transplantation exhibit renal osteodystrophy, and consequently, bone mineral density (BMD) commonly declines immediately after transplantation. 95 Post-transplantation hypophosphataemia can have a detrimental effect on bone mineralization and might contribute to impaired osteoblastogene sis and early osteoblast apoptosis, which further contributes to post-transplantation osteoporosis. 96,97 Data from bone biopsies obtained from renal transplant recipients 22-160 days after transplantation have shown that serum phosphate levels are lower in patients with early osteoblast apoptosis, with serum phosphate levels correlating positively with osteoblast number and correlating negatively with the number of apoptotic osteoblasts.…”
Section: Kidney Transplantationmentioning
confidence: 99%